1999
DOI: 10.1159/000030427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lower Infundibulopelvic Angle, Lower Infundibulum Diameter and Inferior Calyceal Length on Stone Formation

Abstract: The effect of anatomical factors such as lower infundibulopelvic angle (LIPA), lower infundibulum diameter (LID) and inferior calyceal length (ICL) on renal stone formation was investigated. These parameters were measured from noncalculous kidneys of 40 healthy kidney donors. The same parameters from 119 patients with single, unilateral, nonobstructive lower calyceal stone were also measured. LID and ICL were significantly higher in calculous kidneys when compared to the control group. On the other hand, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
2
5
1
Order By: Relevance
“…Although gravitational factor might be more effective than the effect of the upper or middle caliceal variations on stone formation, these findings are also inadequate to explain the lateralization of the stone unless the stone exists in this defective upper or middle calyx. On the hand, there are only few studies, which focus on the etiologic role of these intrarenal anatomical factors (11,12). Gökalp et al compared 119 lower caliceal stoneforming kidneys with 40 healthy controls and they concluded that lower pole IPA was not an important factor for stone formation in lower calyx similar to our study (11).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although gravitational factor might be more effective than the effect of the upper or middle caliceal variations on stone formation, these findings are also inadequate to explain the lateralization of the stone unless the stone exists in this defective upper or middle calyx. On the hand, there are only few studies, which focus on the etiologic role of these intrarenal anatomical factors (11,12). Gökalp et al compared 119 lower caliceal stoneforming kidneys with 40 healthy controls and they concluded that lower pole IPA was not an important factor for stone formation in lower calyx similar to our study (11).…”
Section: Discussionsupporting
confidence: 86%
“…On the hand, there are only few studies, which focus on the etiologic role of these intrarenal anatomical factors (11,12). Gökalp et al compared 119 lower caliceal stoneforming kidneys with 40 healthy controls and they concluded that lower pole IPA was not an important factor for stone formation in lower calyx similar to our study (11).…”
Section: Discussionsupporting
confidence: 86%
“…The difference between two sides was not statistically significant (p>0.05). Go¨kalp et al founded the LID (to be) higher in the stone formers (mean 9.98 mm) and they claimed that the LID was a possible risk factor for stone formation [12]. The difference between our results and those of Go¨kalp et al can be due to the difference in the method of measurements.…”
Section: Discussioncontrasting
confidence: 67%
“…They reported a mean ICL of 32.54 mm for calculous kidneys and 20.99 mm for the noncalculous control group. The difference between these two values was statistically significant [12]. The measurement method was as described by Sampaio and Arago [13].…”
Section: Discussionmentioning
confidence: 99%
“…5 But Gökalp et al observed no significant difference in IUPA between the calculus kidneys with healthy controls and concluded that lower pole IUPA was not an important factor for stone formation in the lower calyx. 18 Kupeli et al also found no difference in IUPA between the calculus kidney and contralateral calculus free kidney. 3 In our study, the infundibulocalyceal length (ICL) of the calculus-bearing kidney was significantly longer than the calculus-free kidney similar to the finding of Gokalp.18 However, Kupeli B et al found no difference in IL between the two sides.…”
Section: Discussionmentioning
confidence: 95%